Evaluation of reliable improvement rates in depression and anxiety at the end of treatment in adolescents. Issue 4 (9th July 2018) - Edbrooke-Childs, Julian; Wolpert, Miranda; Zamperoni, Victoria; Napoleone, Elisa; Bear, Holly
Abstract : Background: Literature has focused on effect sizes rather than individual-level improvement rates to determine how effectively services address burgeoning numbers of adolescents with anxiety and depression. Aims: To consider how many adolescents report reliable improvement in anxiety, depression and comorbid depression and anxiety by end of treatment. Method: The primary outcome was reliable improvement (i.e. change greater than likely the result of measurement error) in self-reported anxiety and depression for N = 4464 adolescents (mean age 14.5 years, s.d. = 1.9; 75% female; 61% White) seen in specialist mental health services in England. Results: In total, 53% of those with anxiety, 44% with depression, and 35% with comorbid depression and anxiety showed reliable improvement. Conclusions: Improvement rates were higher than previously reported, but lower than generally used in advice to the public. There may be a need to set more realistic expectations, including with young people who seek help. Declaration of interest: All authors were involved in the programme of service transformation that this report draws on. M.W. led the outcomes and evaluation group that agreed the approach to measurement used in the initiative.